Appraising the quality standard underpinning international clinical practice guidelines for the selection and care of vascular access devices: a systematic review of reviews - Blanco-Mavillard,I; Rodriguez-Calero,MA; Castro,Sanchez EM; Bennasar-Veny,M; de,Pedro-Gomez J (BMJ Open, 2018)
Objective Catheter-related bloodstream infections are one of the most important adverse events for patients. Evidence-based practice embraces interventions to prevent and reduce catheter-related bloodstream infections in patients. At present, a growing number of guidelines exist worldwide. The purpose of the study was to assess clinical practice guidelines for peripheral and central venous access device care and prevention of related complications.Design Systematic review of clinical practice guidelines: We conducted a search of the literature published from 2005 to 2018 using Medline/PubMed, Embase, CINAHL, Ovid, ScienceDirect, Scopus and Web of Science. We also evaluated grey literature sources and websites of organisations that compiled or produced guidelines. Guideline quality was assessed with the Appraisal of Guidelines for Research and Evaluation, Second Edition tool by three independent reviewers. Cohen’s kappa coefficient was used to evaluate the concordance between reviewers.Results We included seven guidelines in the evaluation. The concordance between observers was substantial, K=0.6364 (95% CI 0.0247 to 1.2259). We identified seven international guidelines, which scored poorly on crucial domains such as applicability (medium 39%), stakeholder involvement (medium 65%) and methodological rigour (medium 67%). Guidelines by Spanish Health Ministry and UK National Institute for Health and Care Excellence presented the highest quality.Conclusions It is crucial to critically evaluate the validity and reliability of clinical practice guidelines so the best, most context-specific document is selected. Such choice is a necessary prior step to encourage and support health organisations to transfer research results to clinical practice. The gaps identified in our study may explain the suboptimal clinical impact of guidelines. Such low adoption may be mitigated with the use of implementation guides accompanying clinical documents.